Loss of Mitochondrial Control Impacts Renal Health - Srivastava, Swayam Prakash; Kanasaki, Keizo; Goodwin, Julie E. (Frontiers in Pharmacology, 2020)
Disruption of mitochondrial biosynthesis or dynamics, or loss of control over mitochondrial regulation leads to a significant alteration in fuel preference and metabolic shifts that potentially affect the health of kidney cells. Mitochondria regulate metabolic networks which affect multiple cellular processes. Indeed, mitochondria have established themselves as therapeutic targets in several diseases. The importance of mitochondria in regulating the pathogenesis of several diseases has been recognized, however, there is limited understanding of mitochondrial biology in the kidney. This review provides an overview of mitochondrial dysfunction in kidney diseases. We describe the importance of mitochondria and mitochondrial sirtuins in the regulation of renal metabolic shifts in diverse cells types, and review this loss of control leads to increased cell-to-cell transdifferentiation processes and myofibroblast-metabolic shifts, which affect the pathophysiology of several kidney diseases. In addition, we examine mitochondrial-targeted therapeutic agents that offer potential leads in combating kidney diseases.